The Use of the Short-Cut Graphic Method of Multiple Correlation: Rejoinder - Black, John D.; Malenbaum, Wilfred (Quarterly Journal of Economics, 1940)
Journal Article Rejoinder Get access John D. Black, John D. Black Harvard University Search for other works by this author on: Oxford Academic Google Scholar Wilfred Malenbaum Wilfred Malenbaum Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 2, February 1940, Pages 346–358, https://doi.org/10.2307/1883342 Published: 01 February 1940